Evaluation of flexural and impact strength of heat-cured poly methyl methacrylate, acrylic, and vertex resins after immersion in different disinfection solutions - Zarah Siddiqui; Lone, Muneeb Ahmed; Bushra Jabeen; Muhammad Khawaja Hammad Uddin; Mah Zul Kaif; Zohra; Ahsan Inayat (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the flexural and impact strength of heat-cured polymethyl methacrylate acrylic and vertex resins after disinfection with alkaline peroxide and sodium hypochlorite solution. Method: The in-vitro, experimental study was conducted at the Dr Ishrat-ul-Ebad Khan Institute of Oral Health Sciences, Karachi, from June 15, 2019, to May 31, 2020, and comprised samples of polymethyl methacrylate and vertex rapid simplified resins that were fabricated using custom metal moulds. The samples were divided into three groups based on the immersion medium: distilled water (control group), alkaline peroxide, and sodium hypochlorite. An immersion time of 6 hours was chosen to simulate one day, thereby three months of continuous immersion represented one year. The samples were then subjected to a 3-point bending test and the Pendulum Impact test to evaluate their flexural and impact strength, respectively. Data was analysed using SPSS 21. Results: There were 90 samples each of polymethyl methacrylate and vertex rapid simplified resins. There was a significant difference in the mean values of impact strength between polymethyl methacrylate and vertex rapid simplified resins following immersion in the disinfectants (p<0.05). However, no significant difference was observed in flexural strength among the groups subjected to immersions in alkaline peroxide and sodium hypochlorite solutions (p>0.05). Conclusion: The immersion in denture cleansers led to an enhancement in both flexural and impact strength for vertex resin simplified resins compared to conventional polymethyl methacrylate denture base materials. Key Words: Denture base materials, Mechanical properties, Disinfectants, Impact strength, Flexural strength.